Evaluation of urban regeneration of worn-out neighborhoods to enhance physical resilience (Case study: The worn-out texture of Faroj city) - ameneh naghdi; Ezzatolah mafi; Mehdi Vatanparast (تحقیقات کاربردی علوم جغرافیایی)
Natural disasters, which are part of the process of human life, pose a major challenge to the sustainable development of human societies. On the other hand, the unsuccessful implementation of urban regeneration schemes has led to a new phenomenon called sustainability in urban projects, with major approaches to sustainability being the revitalization of urban contexts and the emphasis on regeneration. Therefore, in the present study, quantitative planning matrix has been used to evaluate the regeneration of the worn-out neighborhoods of Faraj city in order to enhance the physical resilience. . The research method in this study is descriptive - analytical and for collecting information besides library documents and studies, questionnaire was used which was distributed among a sample of 30 urban experts. Based on data analysis, Shannon entropy was used to evaluate the physical resilience of Faroj's worn-out tissue sites, and then the studied sites were prioritized in terms of physical resilience. Afterwards, the Vicour method was used to rank the Farouq worn-out tissue localities in terms of physical resilience. Based on the Shannon entropy, it has been concluded that neighborhoods 5 and 7 have been prioritized for physical resilience. Also based on the Vikor method, it has been found that out of the four quarters of the worn-out Faroj textile, the number seven neighborhood has the highest resilience.